Analisis Teknologi Corrosion Coupon Dalam Deteksi Korosi Pipa Gas Ruas Gresik-Semarang Dengan Metode FMEA - Ayyasy Nugroho; Rizqi Novita Sari (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
PT Pertamina Gas is a big company that carries out transportation business or as a gas transporter through a transmission pipe. Gas pipes must be monitored regularly so that they do not experience damage, cracks, corrosion or even leaks. This research was conducted to analyze one of the pipe monitoring technologies, namely corrosion coupon monitoring to detect internal pipe corrosion using a failure mode effect (FMEA) method. Through fishbone identification, corrosion is classified into 6 factors, namely material (related to gas), method, people, machines, pipe facilities, and environment. Based on the FMEA method, it was found that the main cause of corrosion is material factors or comes from gas with a defect severity (S) value of 8, occurrence (O) of 6, and detection (D) of 3, with a total RPN of 144. With this research, it is hoped that the company can prioritize these causal factors and carry out corrosion control.